Professional skepticism: The combined effect of partner style and team identity salience. Issue 2 (18th July 2019) - Stevens, Edward; Moroney, Robyn; Webster, John
Abstract : Although essential in the delivery of a high‐quality audit, regulators report their concerns about an apparent lack of professional skepticism exercised by auditors. In an experiment, we use regulatory focus and social identity theories to examine how the style used by a partner (supportive or unsupportive) when allocating a task and team identity salience (high or low) combine to impact skepticism. We find that when team identity salience is high, auditors demonstrate greater skepticism when a partner's style is supportive rather than unsupportive . In additional analysis, we also consider how motivation moderates the effect of partner style and team identity salience on skepticism and retest our hypotheses using a different measure of skepticism. Our results suggest that team identity salience is important when considering the effect of partner style on professional skepticism.